Local vasoregulative interventions impact drug concentrations in the skin after topical laser‐assisted delivery. Issue 10 (20th May 2022) - Wenande, Emily; Gundavarapu, Sarat Chandra; Tam, Joshua; Bhayana, Brijesh; Thomas, Carina N.; Farinelli, William A.; Vakoc, Benjamin J.; Anderson, R. Rox; Haedersdal, Merete
Abstract: Introduction: The ability of ablative fractional lasers (AFL) to enhance topical drug uptake is well established. After AFL delivery, however, drug clearance by local vasculature is poorly understood. Modifications in vascular clearance may enhance AFL‐assisted drug concentrations and prolong drug dwell time in the skin. Aiming to assess the role and modifiability of vascular clearance after AFL‐assisted delivery, this study examined the impact of vasoregulative interventions on AFL‐assisted 5‐fluorouracil (5‐FU) concentrations in in vivo skin. Methods: 5‐FU uptake was assessed in intact and AFL‐exposed skin in a live pig model. After fractional CO2 laser exposure (15 mJ/microbeam, 5% density), vasoregulative intervention using topical brimonidine cream, epinephrine solution, or pulsed dye laser (PDL) was performed in designated treatment areas, followed by a single 5% 5‐FU cream application. At 0, 1, 4, 48, and 72 h, 5‐FU concentrations were measured in 500 and 1500 μm skin layers by mass spectrometry ( n  = 6). A supplemental assessment of blood flow following AFL ± vasoregulation was performed using optical coherence tomography (OCT) in a human volunteer. Results: Compared to intact skin, AFL facilitated a prompt peak in 5‐FU delivery that remained elevated up to 4 hours (1500 μm: 1.5 vs. 31.8 ng/ml [1 hour,   p  = 0.002]; 5.3 vs. 14.5 ng/ml [4 hours, p  = 0.039]). However, AFL's impact was transient, with 5‐FU concentrations comparable to intact skin at later time points. Overall, vasoregulative intervention with brimonidine or PDL led to significantly higher peak 5‐FU concentrations, prolonging the drug's dwell time in the skin versus AFL delivery alone. As such, brimonidine and PDL led to twofold higher 5‐FU concentrations than AFL alone in both skin layers by 1 hour (e.g., 500 μm: 107 ng/ml [brimonidine]; 96.9 ng/ml [PDL], 46.6 ng/ml [AFL alone],   p  ≤ 0.024), and remained significantly elevated at 4 hours ( p  ≤ 0.024). A similar pattern was observed for epinephrine, although trends remained nonsignificant ( p  ≥ 0.09). Prolonged 5‐FU delivery was provided by PDL, resulting in sustained drug deposition compared to AFL alone at both 48 and 72 hours in the superficial skin layer ( p  ≤ 0.024). Supporting drug delivery findings, OCT revealed that increases in local blood flow after AFL were mitigated in test areas also exposed to PDL, brimonidine, or epinephrine, with PDL providing the greatest, sustained reduction in flow over 48 hours. Conclusion: Vasoregulative intervention in conjunction with AFL‐assisted delivery enhances and prolongs 5‐FU deposition in in vivo skin.